Altered acylcarnitine metabolism and inflexible mitochondrial fuel utilization characterize the loss of neonatal myocardial regeneration capacity - E. Kankuri; P. Finckenberg; J. Leinonen; M. Tarkia; S. Björk; J. Purhonen; J. Kallijärvi; M. Kankainen; R. Soliymani; M. Lalowski; E. Mervaala (Experimental and Molecular Medicine, 2023)
Abstract Myocardial regeneration capacity declines during the first week after birth, and this decline is linked to adaptation to oxidative metabolism. Utilizing this regenerative window, we characterized the metabolic changes in myocardial injury in 1-day-old regeneration-competent and 7-day-old regeneration-compromised mice. The mice were either sham-operated or received left anterior descending coronary artery ligation to induce myocardial infarction (MI) and acute ischemic heart failure. Myocardial samples were collected 21 days after operations for metabolomic, transcriptomic and proteomic analyses. Phenotypic characterizations were carried out using echocardiography, histology and mitochondrial structural and functional assessments. In both groups, MI induced an early decline in cardiac function that persisted in the regeneration-compromised mice over time. By integrating the findings from metabolomic, transcriptomic and proteomic examinations, we linked regeneration failure to the accumulation of long-chain acylcarnitines and insufficient metabolic capacity for fatty acid beta-oxidation. Decreased expression of the redox-sensitive mitochondrial Slc25a20 carnitine-acylcarnitine translocase together with a decreased reduced:oxidized glutathione ratio in the myocardium in the regeneration-compromised mice pointed to a defect in the redox-sensitive acylcarnitine transport to the mitochondrial matrix. Rather than a forced shift from the preferred adult myocardial oxidative fuel source, our results suggest the facilitation of mitochondrial fatty acid transport and improvement of the beta-oxidation pathway as a means to overcome the metabolic barrier for repair and regeneration in adult mammals after MI and heart failure.